THE CONSUMPTION OF FRUIT FOR THE YEAR 2007 - Štrbac, Maja; Cvijanović, Drago; Vlahović, Branislav (Economics of Agriculture, 2006)
The consumption of agricultural food products is continuous biological and social process which is of utmost importance for each individual as well as for an entire community. Today, in Serbia and Montenegro, we can witness irregularities regarding proper nourishment of population which affects the health and well-being of entire Nation. Frequent migrations, low wages and increased cost of living, have contributed to continuous negative trends regarding nourishment. The basic goal of this paper is to survey fruit consumption in Serbia and Montenegro per capita, for the period of 1992-2002, in total. Also, this paper will signify state and trends of fruit consumption in Serbia and Montenegro and position of our country in Europe, based on the attained parameters. Particular instances will be compared with previous periods, so as to review the changes in consumption. Based on forecasting value of trends, consumption of fruit in Serbia and Montenegro for the year 2007 will be predicted. This paper will provide theoretical and practical contribution for those responsible to carry out adequate actions to improve fruit production and consumption in Serbia and Montenegro.